Early Medieval Place-Names and Riverine Flood Histories: A New Approach and New Chronostratigraphic Records for Three English Rivers. (August 2020) - Pears, B.; Brown, A.G.; Carroll, J.; Toms, P.; Wood, J.; Jones, R.
Abstract : Environmental information from place-names has largely been overlooked by geoarchaeologists and fluvial geomorphologists in analyses of the depositional histories of rivers and floodplains. Here, new flood chronologies for the rivers Teme, Severn, and Wye are presented, modelled from stable river sections excavated at Broadwas, Buildwas, and Rotherwas. These are connected by the Old English term * wæsse, interpreted as 'land by a meandering river which floods and drains quickly'. The results reveal that, in all three places, flooding during the early medieval period occurred more frequently between AD 350–700 than between AD 700–1100, but that over time each river's flooding regime became more complex including high magnitude single events. In the sampled locations, the fluvial dynamics of localized flood events had much in common, and almost certainly differed in nature from other sections of their rivers, refining our understanding of the precise nature of flooding which their names sought to communicate. This study shows how the toponymic record can be helpful in the long-term reconstruction of historic river activity and for our understanding of past human perceptions of riverine environments.